Sønder Asmindrup-vægindskrift 2: Den gammeldanske del - Heltoft, Lars (Danske Studier, 2025)
Lisbeth Imer and Anders Leegaard Christensen analysed the second line of the Sønder Asmindrup plaster inscription 2 as part of a certificate of debt, and – convincingly so – as a dating in Latin (language). Line 1 in Middle Danish was interpreted by Lis Jacobsen shortly after the discovery of the inscription in 1909. I scrutinise this part of the text and the currently accepted reading. First, the second word of line 1 must read to=ki toki, the preterite subjunctive of taka/take ‘take’. Secondly, I present and discuss two transcriptions and readings of the four first characters of line 2, the focus being on the possible reading as an abbreviation for the verbal form korsede or korsade ‘set a cross’. I find my suggestions in full harmony and coherence with Imer’s and Christensen’s proposal to read the rest of line 2 as a dating in Latin of a contract.